Motivational Effects of the Perceived Image of Non‐governmental Organisations. (4th February 2013) - Pinazo, Daniel; Peris, Rosana; Ramos, Anna; Brotons, Javier
ABSTRACT The motivational effect of the perceived image of non‐governmental organisations (NGOs) was analysed in two studies. Results from the first study, comprising two samples (N = 314 and N = 220), point to three dimensions of the perceived image of NGOs (solidarity, misleading and instrumentality). These dimensions have different effects on intention to collaborate and to recommend others to collaborate. In the second study, with a sample of N = 485, confirmatory analysis confirmed the three‐factor solution as appropriate. The misleading image emerged as a source of reactance to NGO campaigns. Results suggest the importance of promoting the image of solidarity as a motivational strategy. Copyright © 2013 John Wiley & Sons, Ltd.